Investigation into prospects and challenges of implementing inclusive education: a case study at Zengeza four primary in Chitungwiza district. - Mukarati, Anna (Midlands State University, 2019)
This study was designed to investigate prospects and challenges of implementing inclusive education at Zengeza 4 primary in Chitungwiza District .One Administrator and 8 teachers from Zengeza 4 primary participated in the research endeavour. The case study design was selected for use since it allows employment of samples that will be representative of whole populations. The researcher used questionnaires and interviews to gather data for the research. Data was presented using pie charts. . Data was analysed and ultimately discussed using descriptive and narrative approaches. The researcher has concluded that, there are many challenges than prospects in trying to implement inclusive education Zengeza 4 primary. It has recommended in service training of teachers, Supply of resource material to use in the implementation of inclusive education and educating parents on inclusive education. The research has also recommended reviewing of the curriculum for it to support implementation of inclusive education.